RESEARCH ON THE USE OF NANOSCALE APPLICATIONS IN TEACHING THE PHYSICS OF NANOSCALE SEMICONDUCTORS - O‘rinboyeva, Kumushoy Sultanbekovna; Hashimova , Mubinabanu Farhodjonqizi (Educational Research in Universal Sciences, 2023)
In the teaching content of the physics of nano-sized semiconductors course, nano-sized materials and their application in the field, their impact on ecology are studied. In-depth mastering of the structure and theoretical properties of nano-sized materials, To deepen the theoretical knowledge in the classroom in mastering the units, parts, materials, technologies and devices based on the achievements of MST, to increase the interest and passion of students for learning, and to encourage students to learn and master the physics of nano-sized semiconductors. to achieve good practical results in cooperation. It is possible to provide students with interesting information about nanotechnology and to increase their interest in the physics of nano-sized semiconductors. To give them interesting information about nanotechnology. Another advantage of nanotechnology is that computer equipment and mobile phones can be folded like a table cloth and carried in the side pocket. The nanoworld encompasses biology, medicine, energy, material science and other fields. We regularly read and hear about their application to various fields. however, it is known that our ideas about the nanoworld are still very narrow. In fact, nanotechnologies change the usual properties of substances and help to change the world for the better. We cannot imagine our lives without nanotechnologies in most cases. then the demand for nanorobots will increase. When the time comes, nanorobots will perform the tasks that humans can do. In this way, nanotechnology will develop rapidly.